2019
DOI: 10.1016/j.lindif.2019.101752
|View full text |Cite
|
Sign up to set email alerts
|

Differences in text processing by low- and high-comprehending beginning readers of expository and narrative texts: Evidence from eye movements

Abstract: The present study investigated on-line text processing of second-grade low-and high-comprehending readers by recording their eye movements as they read expository and narrative texts. For narrative texts, the reading patterns of low-and high-comprehending readers revealed robust differences consistent with prior findings for good versus struggling readers (e.g., longer firstand second-pass reading times for low-comprehending readers). For expository texts, however, the differences in the reading patterns of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
5
11
0
4
Order By: Relevance
“…We highlight this last non-significant result of Kraal et al (2019) because, as we will see later, one of the results of the present study is consistent with this tendency.…”
Section: Eye-movements During Text Comprehension As a Function Of Tex...supporting
confidence: 89%
See 3 more Smart Citations
“…We highlight this last non-significant result of Kraal et al (2019) because, as we will see later, one of the results of the present study is consistent with this tendency.…”
Section: Eye-movements During Text Comprehension As a Function Of Tex...supporting
confidence: 89%
“…In the particular case of students who are DHH, the literature has documented weaknesses in several domains related to literacy and reading proficiency in terms of discourse skills (Kyle & Cain, 2015;Marschark & Wauters, 2008;Strassman, 1992; see for a review Sullivan et al, 2020), prior knowledge (Convertino et al, 2014), vocabulary (Harris et al, 2017;Herman et al, 2019;Moreno-Pérez et al, 2015), and syntactic skills (Barajas et al, 2016;. All of these findings suggest that the online reading pattern of DHH readers might differ from that of TH readers as a function of their reading proficiency and the type of text they are reading in a similar way that poor and good comprehenders with TH differ (Kraal et al, 2019). In fact, the results of Banner and Wang (2011) mentioned above showed that DHH participants reported using fewer reading strategies in expository than in narrative texts which coincides with the pattern of less efficient or flexible processing strategy by poor readers when facing texts of higher difficulty showed by Kraal et al (2019).…”
Section: Eye-movements During Text Comprehension As a Function Of Tex...mentioning
confidence: 99%
See 2 more Smart Citations
“…This process results in a so-called situation model of the text (Kintsch, 1992;Schnotz, 2014), which consists of both inferences made from the text as well as information from the reader's knowledge base. In this context, the generation of inferences establishes connections between the currently read text and the previously read text or the background knowledge of the reader (Kraal et al, 2019).…”
Section: Models Of Text Comprehensionmentioning
confidence: 99%